Second-Hand Smoke Exposure in Canada: Prevalence, Risk Factors, and Association with Respiratory And Cardiovascular Diseases - Nicholas Vozoris; M Diane Lougheed (Canadian Respiratory Journal)
OBJECTIVES: The aims of the present study were to estimate the prevalence of second-hand smoke exposure in Canada, to identify sociodemographic risk factors for second-hand smoke exposure, and to examine the relationship between second-hand smoke exposure and respiratory and cardiovascular diseases.